Penerapan Sistem Informasi Berbasis Web dan Mobile untuk Manajemen Pasien Diabetes di Klinik Bandar Lor - Dionisius Lexy Putra Winanta; Sulistyo Dwi Sancoko (LPPM STIKI MALANG, 2025)
Diabetes mellitus is a chronic disease that requires continuous monitoring and management. Klinik Pratama Bandar Lor Kediri faces challenges in managing information for diabetic patients, including recording medical history, monitoring blood glucose, facilitating patient–doctor communication, and providing continuous education. Limited access to complete and up-to-date patient data hinders service delivery and complicates clinical decision-making, while patients often struggle to record examination results, adhere to treatment schedules, and obtain optimal consultations. To address these challenges, this study developed DiaCare, a web and mobile based information system built using the prototyping method with Flutter and Firebase. The system integrates key features such as health record management, medication reminders, online consultations, activity tracking with calorie estimation, digital delivery of laboratory results, dietary monitoring, and diabetes-friendly menu recommendations. Functional testing using the black-box method achieved a 100% success rate, validating that all features performed as expected. By enabling patients to self-monitor their condition while maintaining real-time communication with doctors, DiaCare improves efficiency, data accuracy, and patient engagement. The findings suggest that DiaCare has the potential to enhance diabetes management and optimize healthcare services for patients requiring regular monitoring at Klinik Pratama Bandar Lor Kediri.